Evaluasi Proses Pengadaan Barang Menggunakan Metode Value Stream Mapping pada Perusahaan Minyak dan Gas - Angel Olivia Benedikta; Iwan Sukarno (Jurnal Logistik Indonesia, 2020)
Upstream oil and gas industry is one industry that has an important role in the economic movement in Indonesia. Products produced by this industry, namely oil and gas, are one of the largest energy sources in Indonesia. High demand must be supported by rapid exploration and production activities. This activity must be supported by other divisions, one of which is the procurement of goods and services. The main problem currently faced by companies is the length of the procurement process causing the duration of the procurement process to be long. There are 2 factors that cause the duration of procurement duration, namely technical bid evaluation by the user and pre-qualification activities. This research uses quantitative methods by calculating process cycle efficiency and value stream mapping. The results of this study show using the offline method, the resulting process efficiency cycle is 60.59% and the duration of procurement is 67 days. Using the combination of online and offline methods, the process cycle efficiency increased to 73.06% with a procurement duration of 59 days. This shows that the online method can reduce the duration of procurement by up to 8 days with a process cycle efficiency increasing by 12.47%. However, both methods have their advantages and disadvantages so it is proposed that the two methods can be combined to produce less time.